“Evaluacion de soluciones NPK combinados con fertilizantes foliares para mejorar rendimientos y calidad de hoja de lechuga (lactua sativa) en Lamas-San Martín” - Ramírez Tello, Marco Antonio (2005)
The present study is a research work called" Evaluate mixed NPK solution with leave fertilizer (Fert - ali and Bayfolan) on lettuce (Lactuca sativa) in Lamas - San Martin." Whose principal objectives were: 1) To evaluate different macronutrients formulations (N, P, K, Ca and Mg, Mo, Co), vitamins and growth hormones effects applied under fertilirrigation system, looking to improve yield and quality of lettuce leaf in Lamas District; 2) To observe the incidence and foliate Cercosporium illness severity effects. lt was carried out in the land " El Retorno" funds on Remoyacu area of Lamas District and county on San Martin Region. lt has a geographical location of 6° 20' 15" South Latitude, 76° 30' 35" West Longitude and 814 m. o. s. l. Altitude. A randomized completely blocks designed (CBD) with 7 treatments and 4 repetition: T1 (8-16-8 + 2ml Fert-all +2ml Bayfolan), T2(16-24-16 +2ml Fert-all +2ml Bayfolan), T3(24-32-24 +2ml Fert-all + 2ml Bayfolan), T4(17-32-15 + 2ml Fert-all +2ml Bayfolan), T5(15-32-15 + 2ml Fert-all + 2ml Bayfolan), T6( 30-0-0 +2ml Fert all +2ml Bayfolan) and T?(0-0-0). Was used results shows that T5(15-32-15+2ml Fert-all +2ml Bayfolan) with 63.55 % healthy leaves and 3,45 % with Cercosporiun infected leaves giving a net utility of $ 1500. 00 dollars. The infection average for all treatments is more than unity. 1 show that incidence is very high and its and its qualifications are very severe.